Effects of Nitrogen Gas on the Growth of Magnesium Doped Indium Nitride Thin Films via Sol-gen Spin Coating Method - Lee, H. S.; Ng, S. S.; Yam, F. K. (2017)
We report on the growth of magnesium doped indium nitride (InN Mg) thin films via sol-gel spin coating method followed by nitridation process. Special attention was paid to the effects of nitrogen (N2) gas on the nitridation process In this work , the nitridation processes were carried under ammonia with and without nitrogen ambiences. X-ray diffraction results reveal that lnN:Mg thin films deposited with nitrogen ambiences show formation of hexagonal structure InN layer with (1 01) preferential onentation. However, it was found that InN thin film grown under ambient with N2 gas has larger crystallite size (48.27 nm) as compared to that grown under the amb1ent without N2 gas (38.1 0 nm). Field emiss1on scanning electron microscopy results show that both deposited films exhibit coalesced island morphology with hexagonal like structure. Elemental composition analyses by X-rays dispersive spectroscopy reveal that sample grown under ambient with N2 gas has lower oxygen atomic percentage and higher ratio of indium to nitrogen as compared to that grown under ambient without N2 gas. Optical properties of the Mg doped InN thin films were investigated by means of Raman spectroscopy Two allowed Raman modes of wurtzite InN namely, E2(High) and A,(LO) modes, were clearl_y detected for both deposited films Nevertheless, the film grown under the present of N2 gas shows an additional feature corresponding to v4 vibration of the MgN4 tetrahedron at around 564cm1 . The presence of this feature indicates that the magnesium acceptors were activated and the compensation of Mg,n-N (LVM) was occured. Finally, all the results suggest that present of N2 gas during nitridation process will induce better grow of the wurtzite structure Mg-doped InN thin films .